ANALISIS PERBEDAAN NILAI TINGKAT KESEHATAN PADA LPD DESA ADAT SAMBANGAN - putu eka nopiyani; Putu Laba Ari Saka Yana (STEKOM PRESS, 2023)
The purpose of this study was todetermine the cause of the difference in the value of the health level between the LPD Internal Supervisor and the LPLPD of Buleleng Regency at the Sambangan Traditional Village LPD in 2018-2021. The research method uses the CAMEL method. Data collection techniques by means of documentation and interviews. The data analysis technique uses Bali Governor Regulation Number 44 of 2017. The assessment includes Capital, Asset Quality, Management, Earning, Liquidity (CAMEL) factors. The results of the study that: There are differences in the health assessment system in using numbers rounded into thousands and real numbers. In the assessment of Management, the difference is due to the value of general and risk management aspects. The difference in the results of the CPRR calculation that must be established between the Buleleng Regency LPLPD and the LPD Internal Supervisor in the CPRR component in 2020.